Quantitative proteomics reveals oxygen-induced adaptations in Caldalkalibacillus thermarum TA2.A1 microaerobic chemostat cultures - de Jong, Samuel I.; Wissink, Martijn; Yildirim, Kadir; Pabst, Martin; van Loosdrecht, Mark C. M.; McMillan, Duncan G. G. (Frontiers in Microbiology, 2024)
The thermoalkaliphile Caldalkalibacillus thermarum possesses a highly branched respiratory chain.These primarily facilitate growth at a wide range of dissolved oxygen levels. The aim of this study was to investigate the regulation of C. thermarum respiratory chain. C. thermarum was cultivated in chemostat bioreactors with a range of oxygen levels (0.25% O2 -4.2% O2). Proteomic analysis unexpectedly showed both the type I and the type II NADH dehydrogenase present is constitutive.The two terminal oxidases detected were the cytochrome c:oxygen aa3 oxidase, whose abundance was highest at 4.2% O2. The cytochrome c:oxygen ba3 oxidase was more abundant at most other O2 levels, but its abundance started to decline below 0.42% O2. We expected this would result in emergence of the cytochrome c:oxygen bb3 complex or the menaquinol:oxygen bd complex, the other two terminal oxidases of C. thermarum; but neither was detected. Furthermore, the sodium-proton antiporter complex Mrp was downregulated under the lower oxygen levels. Normally, in alkaliphiles, this enzyme is considered crucial for sodium homeostasis. We propose that the existence of a sodium:acetate exporter decreases the requirement for Mrp under strong oxygen limitation.